2001
DOI: 10.1089/10507250152484583
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of the Impact of a Stringent Low-Iodine Diet on Ablation Rates in Radioiodine Treatment of Thyroid Carcinoma

Abstract: Prior analyses of the impact of stringent, preablative low-iodine diets (LIDs) on ablation in patients with differentiated thyroid cancer postthyroidectomy are dated. We retrospectively reviewed first-time, short-term ablation rates for 44 LID patients and 50 patients following a regular diet (RD) who were verbally instructed to avoid salt, seafood, and multivitamins containing iodine. Patients who had undergone ablation were given between 100 and 200 mCi of 131I, depending on the presence of metastases. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
113
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(115 citation statements)
references
References 17 publications
0
113
0
2
Order By: Relevance
“…15,16 These contradictory results notwithstanding, high 24h RAIU is still regarded as an important factor in the success of radioiodine therapy. 11 Decreasing the iodide pool by a low iodine diet 17 or increasing the retention of iodine in the thyroid gland by administering lithium carbonate have previously been proposed by several studies. 18 However, the use of lithium is not a generally accepted option as adjuvant to increase the first-dose success of radioiodine therapy.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 These contradictory results notwithstanding, high 24h RAIU is still regarded as an important factor in the success of radioiodine therapy. 11 Decreasing the iodide pool by a low iodine diet 17 or increasing the retention of iodine in the thyroid gland by administering lithium carbonate have previously been proposed by several studies. 18 However, the use of lithium is not a generally accepted option as adjuvant to increase the first-dose success of radioiodine therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A stringent low-iodine diet was shown to significantly improve ablation success rates in Dutch DTC patients (Pluijmen et al 2003), although this effect was not observed in an American study comparing the stringent diet to a regular diet plus instruction to avoid salt, seafood, and iodine-containing multivitamins (Morris et al 2001b). Moreover, both these studies involved only adults, so the benefits of a low-iodine diet in children remain unconfirmed.…”
Section: Dosimetric Considerationsmentioning
confidence: 98%
“…Apesar de reduzir o valor absoluto de captação, a dieta livre dificilmente impede a realização de estudos diagnósticos, porém, se a intenção é terapêutica, qualquer redução da captação absoluta deve ser evitada. Apesar da difícil mensuração do impacto clínico da dieta pobre em iodo no tratamento ablativo (24), sabe-se que sua adoção reduz efetivamente o iodo disponível no organismo, com a conseqüente redução da iodúria para cerca de um terço do valor sem preparo (24,25) e com o aumento de até duas vezes na dose de radiação absorvida pelos tumores (25,26). Por este motivo, é recomendável manter baixa ingestão de iodo durante 10 a 20 dias pré-tratamento, se possível abaixo de 50µg/dia ou, no mínimo, suspender a ingestão de peixes e frutos do mar, suplementos vitamínicos e reduzir a ingestão de sal e leite.…”
Section: Métodos Para Aumentar a Dose Absorvidaunclassified